1996
DOI: 10.1093/intimm/8.11.1751
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 reverses NK1+ Tcell-defective IL-4 production in the non-obese diabetic mouse

Abstract: Converging data suggest an important role for IL-7 in T lymphocyte maturation as illustrated by the severe T lymphopenia observed in IL-7-deficient mice. We recently reported that IL-7 preferentially promotes the in vitro expansion of a discrete MHC class I-dependent lymphocyte subset comprising both CD4+ and CD4-CD8- TCR alpha beta + cells bearing several NK cells markers such NK1.1 and Ly-49. These T cells, designated as NK1+ T cells, have the unique property among thymocytes of producing large amounts of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…It is therefore conceivable that, particularly in the diabetes model, the pro-Th2 effect of IL-18 treatment results from the capacity of IL-18 to promptly augment IL-4 production by NKT lymphocytes. Indeed, the implication of NKT cells in the control of the autoimmune disease in NOD mice was suggested by the demonstration of their reduced number and function (11,45) and by the prevention of diabetes observed after infusion of NKT cell preparations and in V␣14-J␣281-transgenic NOD mice (46,47).…”
Section: Il-18 Amplifies Early B Cell Activation Induced By In Vivo ␣mentioning
confidence: 99%
“…It is therefore conceivable that, particularly in the diabetes model, the pro-Th2 effect of IL-18 treatment results from the capacity of IL-18 to promptly augment IL-4 production by NKT lymphocytes. Indeed, the implication of NKT cells in the control of the autoimmune disease in NOD mice was suggested by the demonstration of their reduced number and function (11,45) and by the prevention of diabetes observed after infusion of NKT cell preparations and in V␣14-J␣281-transgenic NOD mice (46,47).…”
Section: Il-18 Amplifies Early B Cell Activation Induced By In Vivo ␣mentioning
confidence: 99%
“…It has been shown that IL-7, which is a product of thymic stromal cells, is required for the development and maturation of NKT cells (41,42). Exogenous IL-7 improved the IL-4 production of NOD thymocytes (43), suggesting defective NOD stromal cell functions.…”
Section: Cd44mentioning
confidence: 99%
“…One example is the nonobese diabetic mouse. When compared with normal mice, nonobese diabetic mice have fewer V␣14i NKT cells, which are defective in their capacity to produce antiinflammatory cytokines like IL-4 (5,6). Deficiencies in NKT cells have also been observed in humans with various autoimmune diseases (7,8).…”
mentioning
confidence: 99%